2015
DOI: 10.1111/ijpo.12041
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on outcomes of paediatric acute pancreatitis based on a national administrative database

Abstract: This study demonstrated that obesity significantly influenced the outcomes of paediatric acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
(52 reference statements)
1
12
0
1
Order By: Relevance
“…1 The rising incidence and severity of AP probably reflects rising incidence of obesity in children and increasing awareness among pediatricians. [2][3][4] In spite of the growing awareness, pancreatitis is associated with considerable morbidity in children. Complications in the delayed phase (>4 weeks) of AP include infection and development of pancreatic fluid collections (PFC).…”
Section: Introductionmentioning
confidence: 99%
“…1 The rising incidence and severity of AP probably reflects rising incidence of obesity in children and increasing awareness among pediatricians. [2][3][4] In spite of the growing awareness, pancreatitis is associated with considerable morbidity in children. Complications in the delayed phase (>4 weeks) of AP include infection and development of pancreatic fluid collections (PFC).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, study results indicate that the presence of obesity has negative effects on the trajectory of AP [16, 1924]. Patients with obesity are at a greater risk for fatty infiltration of the pancreas.…”
Section: Effects Of Metabolic Syndromementioning
confidence: 86%
“…Age and obesity have been identified by many studies as easily accessible and negative predictive factors in patients with AP [2730]. An increased risk of early shock, pulmonary and kidney failure, and an extended hospital stay are associated with obesity [16, 1924, 31]. De Waele et al [32] found that in patients with AP, obesity is correlated with disease severity and an increased risk of local complications and mortality.…”
Section: Effects Of Metabolic Syndromementioning
confidence: 99%
“…20 Similar to adults, obese children with AP have worse outcomes compared to non-obese: severe AP, length of stay, medical costs, mortality are significantly higher in obese individuals. 27 The role of obesity as a risk factor for ARP or CP is largely unknown. In a study by Ammann et al, progression to CP in a group of adult patients was slower over time if BMI was >25 and they underwent a drainage surgery previously.…”
Section: Discussionmentioning
confidence: 99%